Analisis Potensi Wisata sebagai Upaya dalam Pengembangan Desa Wisata Berbasis Masyarakat di Desa Wisata Asap Indah Wonosari, Kecamatan Bonang, Kabupaten Demak - Febrianus Rio Sasuwang; Sugiyarto Sugiyarto; Nina Sulistyowati (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify the potential and development strategies for a community-based tourism village in Asap Indah Tourism Village. Data were obtained from observations, interviews, and literature studies. A SWOT analysis was applied to determine the weaknesses, strengths, opportunities, and challenges of developing Bedono tourism village, which can be used to determine the appropriate strategies for community-based tourism development in Bedono Village, Sayung District, Demak Regency. In this research, the process of data reduction, data presentation, and conclusion drawing was carried out simultaneously. The research results concluded that Asap Indah Tourism Village in Wonosari Village, Bonang District, Demak Regency has high potential for development into a community-based tourism village, including fish smoking, water apple agro-tourism, local restaurants, and Bule fishing spots. Based on the SWOT analysis, several strategies can be enhanced to develop Asap Indah tourism village in Wonosari Village, Bonang District, Demak Regency, including strategies for developing tourist attractions, such as creating integrated tourism packages and holding special events; forming a tourism management team; enhancing promotion strategies; improving infrastructure; improving tourism human resources; and strengthening cooperation with stakeholders and investors. If these potentials are developed by involving and empowering the local community, they can increase the value and benefits for the local population in terms of economy, socio-culture, religion, and environment.